ACADEMICIAN BUBUYNA ORUZBAEVA AND THE KYRGYZ LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article will discuss the academician of the National Academy of Sciences of the Kyrgyz Republic, Doctor of Philology, professor, laureate of the State Prize in Science and Technology of the Kyrgyz Republic, Honored Scientist of the Kyrgyz Republic, laureate of the Dank medal, the Manas Order of the 3rd degree, the «mother of the Kyrgyz language» Oruzbaeva Bubuina Omurzakovna. In the article, we will also consider the scientific and theoretical concepts of the scientist about the past tense of the verb in the Kyrgyz language and the formation of words
Keywords: linguistics, Kyrgyz linguistics, professor, academician, verb, past verb, word, word formation, scientific studies